HNF1A gene p.I27L is associated with co-existing preeclampsia in gestational diabetes mellitus. (2nd June 2020) - Beysel, Selvihan; Pinarli, Ferda Alparslan; Eyerci, Nilnur; Kizilgul, Muhammed; Hepsen, Sema; Alhan, Ali; Kan, Seyfullah; Caliskan, Mustafa; Bozkurt, Erhan; Cakal, Erman
Abstract: The association of the FTO gene and HNF1α gene on gestational diabetes mellitus (GDM) and preeclampsia remains unclear. This is the first study to examine whether HNF1α gene and FTO gene were associated with having GDM and preeclampsia in Turkish women. Healthy pregnant women ( n  = 101) and women with GDM ( n  = 169) were included. GDM was divided into two groups as GDM-only ( n  = 90) and GDM-preeclampsia ( n  = 79). Genotyping of HNF1α gene p.I27L, p.A98V, and p.S487N, and FTO gene rs9939609 SNPs were performed using RT-PCR. The frequency of p.S487N, p.A98V, and FTO genotype were similar between the groups ( p  > .05). p.I27L GG-wild, GT, and TT genotype were 56.5%, 36.6%, and 6.9% in controls; 40.0%, 51.1%, and 8.9% in GDM-only; and 26.6%, 51.9%, and 21.5% in GDM-preeclampsia ( p  = .034). TT and GT genotype was more frequent in GDM-preeclampsia than in controls ( p  < .05). GT genotype was increased in GDM-only compared with controls ( p  < .05). TT genotype was more frequent in GDM-preeclampsia than in GDM-only ( p  < .05). p.I27L TT genotype was independently associated with increased blood pressure (BP) and urinary protein. p.I27L TT genotype was associated with increased preeclampsia risk in patients with GDM by increasing BP and urinary protein.